Rethinking overtourism in the post-COVID-19 period: Is demarketing a solution? - Zengin, Burhanettin; Colak, Oguz; Cevrimkaya, Mustafa; Sengel, Umit (Journal of Tourism Management Research, 2023)
At the end of the first quarter of the 21st century, when international arrivals were increasing, the COVID-19 pandemic occurred and turned into a major health crisis that affected the whole world. It has been emphasized that there is a linear relationship between the spread of the pandemic and travel movements from the time the pandemic started to the present day. In this context, the aim of this study is to determine whether there is a relationship between overtourism and pandemic, which has emerged because of increasing touristic travels in recent years. Another aim of the study is to consider demarketing as a solution proposal in the fight against overtourism to prevent health crises such as COVID-19. In this context, 586 news in which the keywords of COVID-19, overtourism and demarket were used together in a certain period were examined and the obtained data were analyzed with the help of MAXQDA (analysis program for qualitative research) qualitative research analysis program. According to the relations between the themes reflected in the results of the study, demarketing can be expressed as a solution proposal for overtourism in the post-COVID-19 period.